Usando o pensamento integrador na definição de portfólios de projetos - Junqueira, José Carlos (2008)
Through transdisciplinarity we can identify large potential for improvement in methodologies traditionally accepted and established in the fields of human knowledge. These gains are related on how the transdisciplinarity proposes the use of research resources of a discipline together with the resources of a second discipline, and assess the object of research with prisms of analysis higher than the sum of sets of each of these disciplines. Considering a transdisciplinary approach, the objective of the current work is to explore the possibilities of implementing the concepts of Complex Thinking, in particular the Integrative Thinking, in a discipline with high needs of a more holistic view - the Portfolio Project Management. The Integrative Thinking can be seen as a strand of Complex Thinking, but shaped and adapted to exact sciences, particularly business administration. There is a great conceptual affinity with issues such as opportunities identification and risk managing, existing in the Portfolio Management, and methodologies of relevance and causality, of the Integrative Thinking. But nowadays, the affinity between the subjects of Portfolio Management and the reductionist methods of problems analysis and resolution is even greater. Through a broader approach on the discipline of Portfolio Management, this essay seeks to propose the use of the evaluation model of situational Integrative Thinking during the evaluation and balancing process of projects portfolio